1982
DOI: 10.1210/endo-110-5-1483
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cartilage Acid Hydrolases by Growth Hormone*

Abstract: The in vivo regulation of three acid hydrolases, namely cathepsin D, cathepsin B, and acid phosphatase, by GH was investigated. The costal cartilage cathepsin D and acid phosphatase activities of hypophysectomized rats were reduced relative to those found in normal controls. Treatment of hypophysectomized animals with GH enhanced rat growth rate and increased these two enzyme activities toward normal levels. Results of pepstatin experiments suggested that the elevated cartilage cathepsin D activity corresponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In addition, WEISSMANN et al (23) showed that lysosomal lysates injected into joints stimulated cartilage cell proliferation. Our finding that growth hormone, a very potent stimulator of cartilage growth, enhanced nonspecific protease activity (7), as well as cartilage cathepsin D and acid phosphatase activities (20) of Hx rat cartilage also supports this contention. It must be emphasized, however, that we have no evidence if the modulation of lysosomal enzymes is a cause or consequence of growth.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, WEISSMANN et al (23) showed that lysosomal lysates injected into joints stimulated cartilage cell proliferation. Our finding that growth hormone, a very potent stimulator of cartilage growth, enhanced nonspecific protease activity (7), as well as cartilage cathepsin D and acid phosphatase activities (20) of Hx rat cartilage also supports this contention. It must be emphasized, however, that we have no evidence if the modulation of lysosomal enzymes is a cause or consequence of growth.…”
Section: Discussionsupporting
confidence: 73%
“…The hormone(s) which may be involved in this developmental phenomenon are yet to be explored. However, we have recently shown that growth hormone enhances cathepsin D and acid phosphatase in cartilage of Hx rats (20). Since growth hormone secretion appears to diminish with age (21,22), the initial decline in cartilage cathepsin D and acid phosphatase activities with age could be related in part to their growth hormone-dependence.…”
Section: Discussionmentioning
confidence: 95%